Hyperhomocysteinemia is a Prior Diator of Congenital Anomalies - Bekzod Ibodov; Umida Shamsieva; Dilshoda Akramova (Genius Journals, 2023)
Currently, the number of congenital diseases is increasing significantly. to prevent and treat the next generation of these congenital diseases, congenital disease markers play an important role as predictors. One of the predictors is maternal serum hyperhomocysteinemia. therefore, we decided to explain in detail the etiology of hyperhomocysteinemia, as well as the toxic effects on the maternal and especially the fetal body, and the mechanism of how hyperhomocysteinemia can cause congenital diseases
Keywords: hyperhomocysteinemia; folate cycle; hypercoagulopathy; endothelial dysfunction